2023
DOI: 10.3390/biom13030556
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Identification and Expression Analysis of Rosa roxburghii Autophagy-Related Genes in Response to Top-Rot Disease

Abstract: Autophagy is a highly conserved process in eukaryotes that degrades and recycles damaged cells in plants and is involved in plant growth, development, senescence, and resistance to external stress. Top-rot disease (TRD) in Rosa roxburghii fruits caused by Colletotrichum fructicola often leads to huge yield losses. However, little information is available about the autophagy underlying the defense response to TRD. Here, we identified a total of 40 R. roxburghii autophagy-related genes (RrATGs), which were highl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 55 publications
1
2
0
Order By: Relevance
“…For example, all OsATG8 genes contained the "ubl-ATG8" domain and motif 1, while all OsATG18 genes contained the "WD40" domain and motif 3 (Figures 2b and 3a). These analytical results show similarities to the analysis of ATG homologs in other species [11,30].…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…For example, all OsATG8 genes contained the "ubl-ATG8" domain and motif 1, while all OsATG18 genes contained the "WD40" domain and motif 3 (Figures 2b and 3a). These analytical results show similarities to the analysis of ATG homologs in other species [11,30].…”
Section: Discussionsupporting
confidence: 71%
“…The first ATG was identified in Saccharomyces cerevisiae, and since then, over 40 ATGs have been identified in eukaryotic organisms [6,7]. In various plant model organisms, such as Arabidopsis thaliana, Zea mays, Oryza sativa, Rosa roxburghii, and Camellia sinensis, ATGs have been extensively studied and found to be involved in growth, development, senescence, stress response, and immunity [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…The commercial formulation 200 gL -1 CAP suspension concentrate (SC) was obtained from FMC Corporation well as antioxidant, anti-aging, and anti-radiation effects (Luo et al, 2023;Wang et al, 2019;Zhang et al, 2022b). Early studies have shown that R. roxburghii juice promotes the formation of foam cells, reduce the accumulation of cholesterol in cells, and thus reduce the incidence of atherosclerosis (Zhang et al, 2001).…”
Section: Reagents and Chemicalsmentioning
confidence: 99%